Vergleich verschiedener Clearance-Berechnungsmethoden bei Verwendung von 99mTc-Mercaptoacetyltriglycin sowie 123J-oder131J-Orthojod-hippursäure - Keske, U.; Cordes, M.; Hosten, N.; Roll, D.; Hunger, J.; Felix, R. (Nuklearmedizin - NuclearMedicine, 1990)
Using labelled MAG3 (n = 172) or OIH (n = 102) the results of three different techniques of calculating renal clearance were compared. The following techniques were used: Tauxe (single plasma concentration determination), Oberhausen (modified, combined partial body and plasma disappearance clearance) and Winkler (partial body clearance). For OIH, linear regression analysis revealed a positive correlation of Tauxe and Oberhausen clearances with a correlation coefficient (r) of 0.90 and a mean ratio (x) Oberhausen/Tauxe clearances of 1.03. For MAG3, the Oberhausen values were found to be significantly lower than the Tauxe values with an equally good correlation. For this radiopharmaceutical the Winkler values were significantly higher than the Tauxe and Oberhausen values. For OIH, no such difference was noted. However, the correlation coefficient was significantly lower. Whereas with the Tauxe method, a mean ratio MAG3-/OIH clearances of 0.62 was observed in an earlier investigation, from the present data a ratio of 0.53 is calculated for the Oberhausen clearance. The difference between the Tauxe and Oberhausen clearances with MAG3 is of importance when comparing clearance values obtained with clearance calculation techniques and for establishing normal values for the MAG3 clearance.